THE IMPLEMENTATION OF RECOGNITION OF PRIOR LEARNING AT LANCANG KUNING UNIVERSITY - Junaidi, Junaidi; Irwanda, Ahmad Ade (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
In today's complex and rapidly changing world, individuals need to be able to improve their competence quickly. However, recognition of learning outcomes outside formal educational institutions is still society’s main focus. As a result, learning outcomes from non-formal, informal education, and work experience are not recognized as they should be, reducing individual motivation and confidence to continue learning throughout life. Lifelong education is a common phenomenon and involves learning through everyday experiences. Learning Recognition is a term that encompasses a range of learning assessment methods outside of formal educational institutions, including approaches such as portfolios, semester credit systems, and competency-based assessments. Improving the accessibility and quality of higher education is one of the national development goals, as mandated in the National Education System Law and the Higher Education Law. Therefore, Lancang Kuning University provides opportunities for the community to participate in education through the Past Learning Recognition (RPL) program. RPL is recognizing a person's learning achievements from formal, non-formal, and informal education, and work experience. The process of equalizing learning outcomes is carried out so that the community can continue their education to a higher level. This study used qualitative descriptive methods by collecting data from sources such as university policies, government regulations, guidebooks, assessment documents, and related literature. The results and discussion of this study revealed that Lancang Kuning University applies RPL Type A, which involves the recognition of part of the credits to continue higher education. Equalization of learning outcomes through RPL provides opportunities for people to learn for life.